The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/feart.2021.700249
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Regional Climate Model Physics Ensemble for Northern Sub-Saharan Africa

Abstract: While climate information from General Circulation Models (GCMs) are usually too coarse for climate impact modelers or decision makers from various disciplines (e.g., hydrology, agriculture), Regional Climate Models (RCMs) provide feasible solutions for downscaling GCM output to finer spatiotemporal scales. However, it is well known that the model performance depends largely on the choice of the physical parameterization schemes, but optimal configurations may vary e.g., from region to region. Besides land-sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…Our findings, therefore, support the suggestion that more than one metric should be provided in the evaluation process (e.g. Chai & Draxler, 2014; Laux et al, 2021a).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings, therefore, support the suggestion that more than one metric should be provided in the evaluation process (e.g. Chai & Draxler, 2014; Laux et al, 2021a).…”
Section: Discussionsupporting
confidence: 89%
“…where CRU and GCM represent the precipitation product from CRU and CMIP6 GCM datasets, respectively, n is the number of observations of the respective time period under consideration, and σ is the standard deviation. Many studies (Guo et al, 2017;Laux et al, 2021;Shiru and Chung, 2021;Oduro et al, 2021) asserted that climate models' ability to capture the daily precipitation variability varies from one model to another depending on its initialization and spatiotemporal resolution. Therefore, to explore the temporal skill of all GCMs relative to the CRU data (You et al, 2017a), we employed interannual variability skill (IVS) for precipitation data accumulated on monthly, annual, and seasonal scales as an alternative to interannual standard deviation (Zhang et al, 2018).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Moreover, we quantify the uncertainties from the boundary conditions, that is, from the different driving GCMs (Figure ) to highlight if and where substantial differences exist. It is found that apart from WRF‐M, all RCMs show a relatively low sensitivity to the driving GCMs, which can be attributed to the effect of internal model physics (Gnitou et al., 2021; Laux, Dieng, et al., 2021).…”
Section: Resultsmentioning
confidence: 99%